Diesel and gasoline like fuel production with minimum styrene content from catalytic pyrolysis of polystyrene. Issue 2 (7th August 2020) - Amjad, Um‐e‐Salma; Ishaq, Manzar; Rehman, Hamood ur; Ahmad, Nabeel; Sherin, Lubna; Hussain, Murid; Mustafa, Maria
Abstract: Pyrolysis of waste polystyrene to generate fuel was carried out to yield pyrolysis oil. For the first time, NiO deposited over ZrO2 carrier as catalyst, was deployed and evaluated in the catalytic pyrolysis. Catalysts based on different loading (2, 5, 10, and 15%) of NiO deposited over ZrO2 carrier were prepared by solution combustion synthesis and tested toward screening of catalytic pyrolysis of PS in semi batch reactor. Based on conversion, yield of oil and low styrene monomer content, the catalytic performance with different loadings was evaluated and optimized. Furthermore, the oil obtained from the best catalysts were analyzed using GC–MS for carbon number distribution, depolymerization reactions, and diesel fuel generation. These catalysts were also characterized using X‐ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), pyridine FTIR, and scanning electron microscopy (SEM) techniques. As compared to thermal pyrolysis, the catalytic pyrolysis process was found to be highly selective toward diesel like fuel generation with minimum styrene monomer formation. Also, 2 and 10% NiO catalyst showed the best catalytic performance in pyrolysis process that could be ascribed to the presence of Lewis and Brönsted acid sites resulting in selectivity for C16 carbon number, diesel fuel generation, and depolymerization reactions.